Energy Crisis: Inflation, Recession, Welfare Loss - Oliver Holtemöller; Stefan Kooths; Torsten Schmidt; Timo Wollmershäuser (Wirtschaftsdienst)
Abstract The German economy is being hit hard by the crisis in the gas markets. Skyrocketing gas prices are drastically increasing energy costs accompanied by a massive withdrawal of purchasing power. This is pushing the German economy into a recession. At the same time, the institutes conclude that there will be no gas shortage in the coming winter under normal weather conditions. Nevertheless, the supply situation remains extremely tight. Against this background, economic output is likely to have already fallen slightly in the third quarter. In the winter half-year, a significant decline is expected due to the rising cost of energy, weakening consumer demand and the weakening global economy.